2012
DOI: 10.1002/bmb.20627
|View full text |Cite
|
Sign up to set email alerts
|

Engagement of students with lectures in biochemistry and pharmacology

Abstract: Academic staff at universities have become concerned about the decrease in student attendance at lectures and the implication of this on student achievement and learning. Few studies have measured actual lecture attendance in a coherent or comprehensive way. The aim of this study was to measure actual lecture attendance of students over two year levels enrolled in two separate science disciplines, biochemistry and pharmacology. The study further sought to determine the factors that influence lecture attendance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
62
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(70 citation statements)
references
References 33 publications
(47 reference statements)
8
62
0
Order By: Relevance
“…17,18,[20][21][22] In addition, accessibility of lecture content in the form of online slides, videos, audios have their own contribution to absenteeism. [23][24][25][26][27] Absenteeism will only allow students not to obtain appropriate information and contact with relevant material (lectures, practical session, clinical skills, etc) that is required for effective learning to occur. In addition, regular attendance in learning activities corresponds to a distributed practice system (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…17,18,[20][21][22] In addition, accessibility of lecture content in the form of online slides, videos, audios have their own contribution to absenteeism. [23][24][25][26][27] Absenteeism will only allow students not to obtain appropriate information and contact with relevant material (lectures, practical session, clinical skills, etc) that is required for effective learning to occur. In addition, regular attendance in learning activities corresponds to a distributed practice system (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…56 Online resources have become readily available over the past decade. 36,[57][58][59][60] It is now common to find recordings of lectures or lecture slides online prior to teaching sessions. These twenty-first century advances create questions around the relevance of lectures delivered in the traditional manner.…”
Section: Availability Of Lecture Slides Prior To Lectures Results In mentioning
confidence: 99%
“…This trend has been repeatedly found in the literature. 6,[33][34][35][36]49,60 However, a number of publications have suggested that attendance does not fall if resources are made available to students prior to lectures. 58,62,63 This trend is reflected in the response to question 2 of our survey.…”
Section: Availability Of Lecture Slides Prior To Lectures Results In mentioning
confidence: 99%
“…financial difficulties lead to students attending paid work rather than class), transport difficulties, inconvenient timetabling (e.g. 8 am), inclement weather, and lack of motivation (Bati, Mandiracioglu, Orgun, & Govsa, 2013;Clark et al, 2011;Davis, Hodgson, & Macaulay, 2012;Hidayat, Vansal, Kim, Sullivan, & Salbu, 2012;Kelly, 2012;Lockwood, Guppy, & Smyth, 2006;Moore, 2008;Newman-Ford et al, 2008;Revell & Wainwright, 2009;Sawon, Pembroke, & Wille, 2012). For students studying Pharmacology, the major reasons for lecture absenteeism were not access to online material, rather they were shown to be timetable clashes, poor quality teaching, unforeseen circumstances (e.g.…”
mentioning
confidence: 99%
“…For students studying Pharmacology, the major reasons for lecture absenteeism were not access to online material, rather they were shown to be timetable clashes, poor quality teaching, unforeseen circumstances (e.g. illness) and assessment pressures (Davis et al, 2012;Hidayat et al, 2012). The last two reasons were more commonly cited for absenteeism in under-performing students (Hidayat et al, 2012).…”
mentioning
confidence: 99%